Primitive Erythropoiesis in the Mouse is Independent of DOT1L Methyltransferase Activity - Malcom, Carrie A.; Ratri, Anamika; Piasecka-Srader, Joanna; Borosha, Shaon; Chakravarthi, V. Praveen; Alvarez, Nehemiah S.; Vivian, Jay L.; Fields, Timothy A.; Karim Rumi, M.A.; Fields, Patrick E. (Frontiers in Cell and Developmental Biology, 2022)
Abstract DOT1-like (DOT1L) histone methyltransferase is essential for mammalian erythropoiesis. Loss of DOT1L in knockout (Dot1l-KO) mouse embryos resulted in lethal anemia at midgestational age. The only recognized molecular function of DOT1L is its methylation of histone H3 lysine 79 (H3K79). We generated a Dot1l methyltransferase mutant (Dot1l-MM) mouse model to determine the role of DOT1L methyltransferase activity in early embryonic hematopoiesis. Dot1l-MM embryos failed to survive beyond embryonic day 13.5 (E13.5), similarly to Dot1l-KO mice. However, when examined at E10.5, Dot1l-MM embryos did not exhibit overt anemia like the Dot1l-KO. Vascularity and the presence of red blood cells in the Dot1l-MM yolk sacs as well as in the AGM region of Dot1l-MM embryos appeared to be similar to that of wildtype. In ex vivo cultures of yolk sac cells, Dot1l-MM primitive erythroblasts formed colonies comparable to those of the wildtype. Although ex vivo cultures of Dot1l-MM definitive erythroblasts formed relatively smaller colonies, inhibition of DOT1L methyltransferase activity in vivo by administration of EPZ-5676 minimally affected the erythropoiesis. Our results indicate that early embryonic erythropoiesis in mammals requires a DOT1L function that is independent of its intrinsic methyltransferase activity.